2011
DOI: 10.1002/stem.751
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Transmissible Animal Tumors as Models of the Cancer Stem-Cell Process

Abstract: Tasmanian devil facial tumor disease (DFTD) and canine transmissible venereal tumor (CTVT) are highly unusual cancers capable of being transmitted between animals as an allograft. The concept that these tumors represent a cancer stem-cell process has never been formally evaluated. For each, evidence of self-renewal is found in the natural history of these tumors in the wild, tumor initiation in recipient animals, and serial transplantation studies. Additional data for stem-cell-specific genes and markers in DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
(125 reference statements)
2
9
0
Order By: Relevance
“…Although the cancer progenitor cells are thought to be different according to the two theories, that is, somatic cells and CSCs, respectively, both theories portray cancer progression as the accumulation of genetic modifications (mutations and epigenetic alterations) and selection for, and subsequent expansion of, clones with highest survival and reproductive (proliferative) advantage. Interestingly, although transmissible animal cancers have been proposed to provide excellent model systems of the CSC process , a preliminary study focusing on the expression profiles of embryonic stem cell and pluripotent germ cell specific genes could not confirm the existence of CSCs in devil facial tumours . However, to univocally confirm or exclude the role of CSCs in transmissible cancer progression, additional experiments must be conducted, including identification of (i) a population of potential CSCs from fresh tumour samples and/or primary cell cultures and (ii) sarcosphere formation and self‐renewal assays, followed by gene signature analyses of stem cell markers, and (iii) once a possible stem cell population has been identified, the evaluation of number of cells required from the enriched CSCs and from primary cancers to initiate a tumour when xenotransplanted into immuno‐compromised mice would be the ultimate proof of CSC existence .…”
Section: Transmissible Cancers Adapt To Both Their Micro‐environment mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the cancer progenitor cells are thought to be different according to the two theories, that is, somatic cells and CSCs, respectively, both theories portray cancer progression as the accumulation of genetic modifications (mutations and epigenetic alterations) and selection for, and subsequent expansion of, clones with highest survival and reproductive (proliferative) advantage. Interestingly, although transmissible animal cancers have been proposed to provide excellent model systems of the CSC process , a preliminary study focusing on the expression profiles of embryonic stem cell and pluripotent germ cell specific genes could not confirm the existence of CSCs in devil facial tumours . However, to univocally confirm or exclude the role of CSCs in transmissible cancer progression, additional experiments must be conducted, including identification of (i) a population of potential CSCs from fresh tumour samples and/or primary cell cultures and (ii) sarcosphere formation and self‐renewal assays, followed by gene signature analyses of stem cell markers, and (iii) once a possible stem cell population has been identified, the evaluation of number of cells required from the enriched CSCs and from primary cancers to initiate a tumour when xenotransplanted into immuno‐compromised mice would be the ultimate proof of CSC existence .…”
Section: Transmissible Cancers Adapt To Both Their Micro‐environment mentioning
confidence: 99%
“…lysozyme‐40, vimentin, desmin, nestin, etc. ) have revealed that despite the clonal nature of vertebrate transmissible cancers, there is significant heterogeneity of lineage marker expression both within the tumour cell population and between individual tumours (reviewed by O'Neill ). The observed high intra‐tumour and inter‐tumour phenotypic heterogeneity on stable genomic backgrounds demonstrates that tumour cells engage in an incessant crosstalk between each other and their micro‐environment and phenotypically adjust to the changes of the surrounding stroma.…”
Section: Tumour Macro‐environment Shapes the Evolution Of Transmissibmentioning
confidence: 99%
“…Another example of a cancer thought to be NC-origin is Ewing sarcoma, an aggressive bone and soft tissue tumors [6] . Considering a recent idea of cancer stem cells [7] , [8] , NCCs may share molecular features common to malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Since BCSCs are considered to be the root of metastasis, promote recurrence of the malignancy, and are resistant to traditional therapy [24-27], we tested this profile in a series of 198 consecutive patients who were diagnosed with early breast cancer. The results showed that the 41-gene profile performed best as a predictor of DMFS by classifying patients into high-EL and low-EL groups.…”
Section: Discussionmentioning
confidence: 99%